2009
DOI: 10.1073/pnas.0902910106
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of primase RepB′ encoded by broad-host-range plasmid RSF1010 that replicates exclusively in leading-strand mode

Abstract: For the initiation of DNA replication, dsDNA is unwound by helicases. Primases then recognize specific sequences on the template DNA strands and synthesize complementary oligonucleotide primers that are elongated by DNA polymerases in leading-and lagging-strand mode. The bacterial plasmid RSF1010 provides a model for the initiation of DNA replication, because it encodes the smallest known primase RepB (35.9 kDa), features only 1 single-stranded primase initiation site on each strand (ssiA and ssiB, each 40 nt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
66
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(69 citation statements)
references
References 38 publications
3
66
0
Order By: Relevance
“…assists p49 from another molecule) and that two primase molecules are associated at least during dinucleotide synthesis. There is a precedent of that mechanism; the helical domain of prokaryotic primase Rep␤Ј is flexibly tethered to the catalytic domain of the same polypeptide and plays the critical role in synthesis initiation, like p58 C (46). Consistent with this model, it was recently shown that the Ctf4 trimer that couples Prim-Pol ␣ to the eukaryotic replisome can bind two Pol ␣ molecules (47).…”
Section: Discussionmentioning
confidence: 53%
“…assists p49 from another molecule) and that two primase molecules are associated at least during dinucleotide synthesis. There is a precedent of that mechanism; the helical domain of prokaryotic primase Rep␤Ј is flexibly tethered to the catalytic domain of the same polypeptide and plays the critical role in synthesis initiation, like p58 C (46). Consistent with this model, it was recently shown that the Ctf4 trimer that couples Prim-Pol ␣ to the eukaryotic replisome can bind two Pol ␣ molecules (47).…”
Section: Discussionmentioning
confidence: 53%
“…According to the data in the literature and our results, we can propose that DNA primases from other species, including phages, bacteria, and archaea, bind DNA/RNA in a similar way, where the flexibly tethered accessory domain participates in binding of the template and the initiating NTP (37)(38)(39)(40)(41)(42). Depending on the organism studied, the functional counterpart of p58 C may be located on the catalytic or a different subunit, may contain an [FeS]-cluster or zinc or none of them, and may work in cis or trans orientation.…”
Section: Discussionmentioning
confidence: 95%
“…The structural data demonstrate that the RNA priming activity of primase is encoded within a unique protein fold that is unrelated to that of other DNA or RNA polymerases. The polymerase fold of archaeal/ eukaryotic PriS has also been identified in an archaeal replicase with combined primase and polymerase activity (17), a bacterial plasmid primase (18), and the polymerase component of bacterial DNA repair ligase D (19). Conservation of aspartic residues in the PriS sequence and site-directed mutagenesis studies indicate that primase uses metal ion-dependent catalysis for nucleotide polymerization (20).…”
mentioning
confidence: 99%